Internet gambling is a predictive factor of Internet addictive behavior among Cypriot adolescents - Critselis, Elena; Janikian, Mari; Paleomilitou, Noni; Oikonomou, Despoina; Kassinopoulos, Marios; Kormas, Georgios; Tsitsika, Artemis K. (My University, 2013)
Background and aims: Adolescent Internet gambling is associated with concomitant addictive behaviors. This study aimed to assess the prevalence of Internet gambling practices, its impact upon psychosocial development and to evaluate the association between gambling practices and Internet addictive behavior among Cypriot adolescents. Methods: A cross-sectional study was conducted in a convenience sample (n = 805) of adolescents attending selected public schools (9th and 10th grades) in Cyprus. Anonymous self-completed questionnaires were used including the Internet Addiction Test and the Strengths and Difficulties Questionnaire. Results: Among the study population (n = 805), approximately one third (n = 28; 34.9%) reported Internet gambling. Internet gamblers were twice as likely to utilize Internet café portals (adjusted odds ratio for gender and age, AOR: 2.13; 95% confidence interval, 95% CI: 1.56-2.91) for interactive game-playing (AOR: 6.84; 95% CI: 4.23-11.07), chat-rooms (AOR: 2.57; 95% CI: 1.31-4.85), and retrieval of sexual information (AOR: 1.99; 95% CI: 1.42-2.81). Among Internet gamblers 26.0% (n = 73) reported borderline addictive Internet use and 4.3% (n = 12) addictive behavior. Internet gamblers more often had comprehensive psychosocial and emotional maladjustment (AOR: 4.00; 95% CI: 1.97-8.13), including Abnormal Conduct Problems (AOR: 3.26; 95% CI: 2.00-5.32), Emotional Symptoms (AOR: 1.78; 95% CI: 1.02-3.11), and Peer Problems (AOR: 2.44; 95% CI: 1.08-5.48) scores. The multivariate regression analyses indicated that the single independent predictor associated with Internet addictive behavior was Internet gambling (AOR: 5.66; 95% CI: 1.45-22.15). Discussion: Internet gambling is associated with addictive Internet use, as well as emotional maladjustment and behavioral problems, among Cypriot adolescents. Conclusions: Longitudinal studies are needed to elucidate whether Internet gambling constitutes a risk factor for the development of Internet addictive behavior among adolescents.
Keywords: Internet; Addictive behavior; Adolescent; Gambling; Psychosocial aspects